The Effect of Vermicompost Application on Yield and Nutrient Concentration of Oily Rose - Fatih Kural; Ali Coşkan (Turkish Journal of Agriculture: Food Science and Technology, 2023)
In the study, the impact of employing vermicompost to boost oil rose (Rosa damascena Mill.), a native of Isparta province, to improve yield and nutrient content, was explored. Four different doses (V0: 0 kg ha-1, V1: 1000 kg ha-1, V2: 2000 kg ha-1, and V3: 3000 kg ha-1) of vermicompost were tested in the field conditions at 3 replicates. Vermicompost was applied to the canopy projection area and incorporated into the soil. Flower harvest was started on April 30, 2018, and throughout 20 days, the blooming flowers were collected and weighed daily basis. Following the harvest, leaf samples were collected from the plants, and the concentrations of certain macro and micronutrients were assessed.The study's findings demonstrated that applying vermicompost boosted the yield of oily rose blooms. The greatest yield value was determined to be 5850 kg ha-1 at a vermicompost dose of 2000 kg ha-1, which was 660 kg ha-1 greater than the control application. It was observed that vermicompost treatments had no significant influence on plant nutrient concentrations.  This condition is assumed to be related to the removal of minerals from the plant during harvest. The findings indicate that the usage of vermicompost can contribute in the production of oil roses, and a dose of 2000 kg ha-1 can be suggested. This research establishes the feasibility of employing vermicompost in oil rose cultivation and sets the framework for future research.